ECONOMICS ETHICS IN THE FATWA OF ISLAMIC ECONOMICS - Maksum, Muhammad (Al-Ulum, 2015)
The fatwa by the National Sharia Board (Dewan Syariah Nasional/DSN) of Indonesian Ulema Council (Majlis Ulama Indonesia/MUI) and The Sharia Advisory Council of Central Bank of Malaysia/Bank Negara Malaysia (BNM) on Islamic economics is dominated by its ethical aspects. The prohibition of riba (interest), for instance, is an Islamic ethic which is mostly set in both institutions. In this case, the Legal consideration contains more ethics than fatwa verdicts. The ethics in the legal consideration is commonly based on the basic ethical principles of The Noble Quran, the hadith and the Islamic jurisprudence. In the meantime, the ethics for the object of contract in DSN is mentioned more in the fatwa verdict than in their legal consideration while the ethics for contract performer is equally found in both areas. This thesis is discovered by reading the DSNs fatwa from 2000 t0 2010 and the MPAs fatwa from 1997 to 2010. Once identified, the ethics in both institutions is classified into a particular category. As the result, this research generates a great implication on the dominant aspect of Islamic ethics in its legal formal.-----Fatwa Dewan Syariah Nasional (DSN) Majelis Ulama Indonesia (MUI) dan Majelis Penasihat Syariah (MPS) Bank Negara Malaysia (BNM) tentang ekonomi syariah didominasi aspek etika Syariah. Larangan riba merupakan etika syariah yang paling banyak ditetapkan dalam dua fatwa tersebut. Bagian konsideran hukum lebih banyak memuat etika ketimbang bagian putusan fatwa. Etika dalam konsideran hukum umumnya menyangkut prinsip-prinsip dasar etika yang bersumber dari Alquran, hadis, dan kaidah fikih. Etika untuk objek akad dalam fatwa DSN lebih banyak disebutkan pada putusan fatwa dari pada konsideran hukumnya. Etika untuk pelaku akad dalam fatwa MPS ditemukan hampir seimbang dalam konsideran dan putusannya. Tesis tersebut ditemukan melalui pembacaan terhadap fatwa DSN tahun 2000-2010 dan fatwa MPS tahun 1997-2010. Setelah diidentifikasi, etika-etika yang terdapat dalam fatwa DSN dan MPS dikelompokkan dalam kategori tertentu. Penelitian ini berimplikasi pada kuatnya aspek etika syariah yang dominan pada sisi legal formalnya.